Faustovstvo v dobi izgubljene nedolžnosti - Knop, Seta (Primerjalna književnost, 2006)
Faustianism in the Age of Lost Innocence. The article analyses the answers of 20th century Fausts to the "modern" Faustian project of everlasting progress, which has nowadays in many ways proved to be a failure. In the light of the dialectics of Enlightenment and reception theory, it focuses on three literary works, written in the years immediately before or during the second world war: Thomas Mann's paradigmatic "German" Faust, Mikhail Bulgakov's disheartened "Russian" Faust and Paul Valéry's disenchanted "French" Faust.
Keywords: Mann, Thomas, 1875-1955; Bulgakov, Mihail, 1891-1940; Valéry, Paul, 1871-1945; literarni liki; Faust; faustovstvo; literarne študije